Identification of Functional Genetic Determinants of Cardiac Troponin T and I in a Multiethnic Population and Causal Associations With Atrial Fibrillation. (4th November 2021) - Yang, Yunju; Bartz, Traci M.; Brown, Michael R.; Guo, Xiuqing; Zilhão, Nuno R.; Trompet, Stella; Weiss, Stefan; Yao, Jie; Brody, Jennifer A.; Defilippi, Christopher R.; Hoogeveen, Ron C.; Lin, Henry J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Elevated cardiac troponin levels in blood are associated with increased risk of cardiovascular diseases and mortality. Cardiac troponin levels are heritable, but their genetic architecture remains elusive. Methods: We conducted a transethnic genome-wide association analysis on high-sensitivity cTnT (cardiac troponin T; hs-cTnT) and high-sensitivity cTnI (cardiac troponin I; hs-cTnI) levels in 24 617 and 14 336 participants free of coronary heart disease and heart failure from 6 population-based cohorts, followed by a series of bioinformatic analyses to decipher the genetic architecture of hs-cTnT and hs-cTnI. Results: We identified 4 genome-wide significant loci for hs-cTnT including a novel locus rs3737882 in PPFIA4 and 3 previously reported loci at NCOA2, TRAM1, and BCL2 . One known locus at VCL was replicated for hs-cTnI. One copy of C allele for rs3737882 was associated with a 6% increase in hs-cTnT levels (minor allele frequency, 0.18; P =2.80×10 −9 ). We observed pleiotropic loci located at BAG3 and ANO5 . The proportions of variances explained by single-nucleotide polymorphisms were 10.15% and 7.74% for hs-cTnT and hs-cTnI, respectively. Single-nucleotide polymorphisms were colocalized with BCL2 expression in heart tissues and hs-cTnT and with ANO5 expression in artery, heart tissues, and whole blood and both troponins. Mendelian randomization analyses showed that genetically increased hs-cTnT and hs-cTnI levels were associated with higher odds of atrial fibrillation (odds ratio, 1.38 [95% CI, 1.25–1.54] for hs-cTnT and 1.21 [95% CI, 1.06–1.37] for hs-cTnI). Conclusions: We identified a novel genetic locus associated with hs-cTnT in a multiethnic population and found that genetically regulated troponin levels were associated with atrial fibrillation.